Lessons from genomic profiling: towards a molecular-based classification of ovarian Sertoli-Leydig cell tumour$dcorrespondence - Kommoss, Felix (Histopathology, 2024)
Currently available molecular data support a dichotomous classification of Sertoli-Leydig cell tumours (SLCTs) based on DICER1 mutational status. This correspondence suggests a possible roadmap towards a molecular-based classification of SLCT.image
Gesehen am 16.02.2024